(untitled) (American Journal of Business Management, Economics and Banking, 2025)
This article analyzes the importance and methods of organizing internal audit of investment activities. Internal audit is considered an important tool for improving the efficiency of investment processes, ensuring the rational use of financial resources, and minimizing risks. The article covers key areas such as planning investment projects, reviewing financial reports, and improving the internal control system. Additionally, recommendations are provided for identifying and eliminating shortcomings in investment activities through internal audit. This study aims to develop internal audit to enhance effective management of investments and reduce financial risks in organizations.